3D Photogrammetry Modeling Highlights Efficient Reserve Effect Apparition After 5 Years and Stillness After 40 for Red Coral (Corallium rubrum) Conservation in French MPAs - Richaume, Justine; Cheminée, Adrien; Drap, Pierre; Bonhomme, Patrick; Cadene, Frederic; Ferrari, Bruno; Hartmann, Virginie; Michez, Noëmie; Bianchimani, Olivier (Frontiers in Marine Science, 2021)
Imaging the marine environment is more and more useful to understand relationships between species, as well as natural processes. Developing photogrammetry allowed the use of 3D measuring to study populations dynamics of sessile organisms at various scales: from colony to population. This study focuses on red coral (Corallium rubrum), as known as precious coral. Metrics measured at a colony scale (e.g., maximum height, diameter and number of branches) allowed population understanding and a comparison between an old (Cerbère-Banyuls reserve) vs. a new (Calanques National Park) MPA. Our results suggested a 5-year time step allows the appearance of a significant difference between populations inside vs. outside the Calanques National Park no-take zones. Red coral colonies were taller and had more branches inside no-take zones. A significant difference was still observable for the populations inside the Cerbère-Banyuls reserve after 40 years of protection, reflecting the sustainability and effectiveness of precautionary measures set by the reserve. The impacts at the local level (mechanical destruction) and those presumed to occur via global change (climatic variations) underline the need to develop strategies both to follow the evolutions of red coral populations but also to understand their resilience. Photogrammetry induced modeling is a time and cost effective as well as non-invasive method which could be used to understand population dynamics at a seascape scale on coralligenous reefs.